A Comprehensive Review on Solar Powered Electric Vehicle Charging System. Issue 1 (2nd January 2018) - Khan, Saadullah; Ahmad, Aqueel; Ahmad, Furkan; Shafaati Shemami, Mahdi; Saad Alam, Mohammad; Khateeb, Siddiq
Abstract: Electric vehicles (EVs) are becoming increasingly popular in many countries of the world. EVs are proving more energy efficient and environmental friendly than ICEVs. But the lack of charging stations restricts the wide adoption of EVs in the world. As EV usage grows, more public spaces are installing EV charging stations. On the other hand, if EVs are charged via existing utility grid powered by fossil fuel-based generation system, then it affects the distribution system and could not be environmentally friendly. As solar has great potential to generate the electricity from PV panel, the charging of EVs from PV panels would be a great solution and also a sustainable step toward the environment. This paper presents a comprehensive analysis of solar PV-EV charging systems and deployment in the world. Analytical methods were proposed to obtain information about EV charging behavior, modes of charging station operation, and geolocation of charging station users. The methodology presented here was time- and cost-effective, and very helpful to the researchers and students in this field. Abstract :